Age at first mating on lifetime productivity of corriedale ewes in southern Brazil - de Oliveira, Nelson Manzoni; Kennedy, Jonh P.; Selaive-Villarroel, Arturo B. (Pesquisa Agropecuaria Brasileira, 1993)
A total of five different Corriedale flocks (respectively initiated in years 1976–1980), totalling 2,561 breeding ewes, were first mated at 19-20 or 30-31 months of age. Lifetime production data on: a) fleece weight and its components (as measured by greasy fleece weight, washing yield, clean fleece weight, fibre diameter and staple length), b) reproductive performance (as evaluated by the number of lambs weaned/ewe joined and lamb weaning weight/ewe joined) and c) ewe liveweight, were investigated within each flock up to 1982. Considering the environment provided in the study, the results indicated that earlier mating in these Corriedale ewes depressed their subsequent wool quantity, yet there was no appreciable effect upon wool quality components and reproductive performance. It has been concluded that when the early joining management is to be adopted, it is worthwhile considering the relative economic importance of the production components examined. These would indicate whether or not the income derived from the extra lambs produced at the early joining would compensate the losses in wool weight.